Analysis of coal quality as fuel for steam power plants in Langkat Regency based on the proximate test - Alfath Khoir Nst; Sayuthi, Muhammad; Amani, Yasir; Habibi, Muhammad; Faisal, Faisal; Hidayat, Heindrix (Journal of Mechanical Engineering and Fabrication, 2025)
Coal quality assessment is crucial for determining its suitability as a fuel for power generation and industrial applications. Such evaluation generally involves proximate and ultimate analyses. The proximate analysis provides information on moisture, volatile matter, fixed carbon, and ash content, whereas the ultimate analysis identifies elemental composition such as carbon, hydrogen, oxygen, nitrogen, and sulfur. Geological factors, including age, temperature, and pressure during formation, strongly influence coal quality. This study aims to evaluate the effect of particle size on coal quality using grain sizes of 40 and 60 mesh, analyzed according to ASTM standard procedures. The results indicate that coal with a grain size of 40 mesh contains, on average, 22.22% moisture, 5.83% ash, 37.54% volatile matter, and 34.15% fixed carbon. In contrast, coal with a grain size of 60 mesh exhibits 20.45% moisture, 6.80% ash, 42.77% volatile matter, and 29.99% fixed carbon. These findings highlight the significant influence of particle size on the proximate characteristics of coal, which can affect its combustion behavior and potential applications in power plants and other industries